(untitled) (Sebha University Conference Proceedings, 2022)
This research aims to shed light on INTERPOL’s role in the anti-corruption as well as illustrating the most important constraints that it faces. Consequently, firstly, the concept of corruption, and the emergence of INTERPOL were examined. Secondly, the organization’s anti-corruption mechanisms were addressed, as well. Therefore, the researcher has adopted the inductive and descriptive approaches. It is noted that INTERPOL has played a dual role in the anti-corruption movement since it was identified as a priority criminal area in 2007. From one hand, INTERPOL seeks to detect and seize the crime of corruption. On the other hand, INTERPOL tries to recover its revenues through its tools that facilitate cooperation and information exchange among Member States’ law enforcement agencies. Moreover, INTERPOL provides training and support to its cadres. Nevertheless, INTERPOL faces some challenges that impede its work in anti-crime in general and corruption in particular.